2023
DOI: 10.13057/biodiv/d240169
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical identification of mango (Mangifera indica L.) and other fruit trees mentioned in Old Javanese Ramayana (10th century Java, Indonesia)

Abstract: Abstract. Mulyanto D, Supangkat B, Nurseto HE, Iskandar J. 2023. Ethnobotanical identification of mango (Mangifera indica L.) and other fruit trees mentioned in Old Javanese Ramayana (10th century Java, Indonesia). Biodiversitas 24: 609-616. Among the 2778 stanzas in Old Javanese Ramayana (OJR), only 46 (1.6%) mentioned fruit trees. There are 63 Old Javanese phytonyms for fruit or fruit tree and only 12 (19%) of them are Sanskrit in origin. Fifty-six species from 44 genera and 26 families are identified, highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…This agrees with the work of Metusala et al (2020) who reported the presence of mango trees all over Indian places such as village settlements, wild forests, royal gardens, farms, reliefs of Borobudur Temple, etc. Similar results were obtained by Mulyanto et al (2023) who recorded 63 names of mango species in Indonesia.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This agrees with the work of Metusala et al (2020) who reported the presence of mango trees all over Indian places such as village settlements, wild forests, royal gardens, farms, reliefs of Borobudur Temple, etc. Similar results were obtained by Mulyanto et al (2023) who recorded 63 names of mango species in Indonesia.…”
Section: Discussionsupporting
confidence: 85%
“…Ascertaining the origin and genetic diversity of these cultivated varieties will require genetic analyses, but the sampled communities were convinced about the importance of preserving the landraces they cultivated knowing that they had been passed down through many generations (Malik et al 2012;Ravishankar et al 2000;Rey et al 2006). The ethnobotanical surveys allow us to understand the relationship between human beings and plant species (Fatur 2019;Petran et al 2020;Liu et al 2021;Mulyanto et al 2023). We can infer indigenous knowledge of mango and sweet orange species based on their current utilization and benefits to people who cultivate and use them (Iwu 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies on ethnobotanical aspect of ancient literary works from pre-Islamic Java (Jákl, 2015a;2015b;Hoogervorst & Jákl, 2020;Mulyanto et al, 2023). However, these works, similar to the majority of studies conducted on ancient Java, relied heavily on texts originating from Middle and East Java or Bali Island.…”
Section: Introductionmentioning
confidence: 99%